Visible light mediated cyclization of tertiary anilines with maleimides using a supported iridium complex catalyst. Issue 32 (5th April 2017) - Peng, Feng; Zhi, Peng; Ji, Heng; Zhao, Huan; Kong, Fen-Ying; Liang, Xue-Zheng; Shen, Yong-Miao
Abstract : The synthesis of a novel supported iridium complex catalyst and its efficient application in the visible light mediated cyclization of tertiary anilines and maleimides. Abstract : The novel supported iridium complex catalyst was synthesized through the immobilization of the iridium complex onto vinylpyridine and divinylbenzene copolymer. In order to avoid the iridium releasing, vinylpyridine was used to provide the chelating sites. The catalytic activity was investigated through the visible light mediated cyclization of tertiary anilines and maleimides. The catalyst showed high activity and stability with the average isolated yield over 50%. The heterogeneous process greatly simplified catalyst recovery and product purification, which was quite superior to homogeneous iridium complexes. Compared with transition metal complexes such as Ru(bpy)3 Cl2 or Ir(ppy)2 (dtbbpy)PF6, advantages of this supported iridium complex catalyst as the photocatalyst include high hydrophobic BET surface and catalytic activity, low cost, ease of recovering and being able to be used for at least four times without significant decay of catalytic activity.